Preceptors' perceptions of assessing clinical associate students at district hospital sites - Aloysious Kakia; Ian Couper (AOSIS, 2021)
Background: Preceptors are key stakeholders in distributed health professions' education. They supervise students in the clinical setting to enable them to have a practical experience with patients, and they assess students' skills at the highest tier of clinical assessment. The university where this study was done conducts a distributed Bachelor of Clinical Medical Practice course on a distributed platform which is dependent on preceptors at the training sites. Understanding the perceptions of preceptors, as major stakeholders, regarding the student assessment they do will assist the faculty to provide better support and development that might be needed and assist in maximising the benefits of distributed training. Aim: The aim of this study was to explore the perceptions of preceptors regarding assessing clinical associate students at district hospitals in the Bachelor of Clinical Medical Practice programme. Setting: The study was conducted at a rural university in the Eastern Cape province of South Africa. Methods: This was a qualitative study involving nine preceptors who were purposively selected from three district hospital training sites based on their involvement in assessing clinical associate students. Semi-structured interviews were conducted, recorded, transcribed and thematically analysed. Results: Four themes emerged from thematic analysis: assessment issues, preceptor issues, student issues and university support issues. Preceptors are committed and enthusiastic in training and assessing the clinical associate students but require input from the university in terms of training and ongoing support. Conclusion: Lack of training threatens the validity of preceptor assessment. Academic institutions should train and support preceptors to enable them better to fulfil their roles.